Green Footprint Through the Development of a Sustainability Reporting Concept for Karangpring Village - Siska Aprilia Oktaviani; Fitriya Andriyani; Oryza Ardhiarisca; Prillinaya Yudhistira; Berlina Yudha Pratiwi; Dessy Putri Andini (STIE Malangkucecwara, 2026)
This study aims to examine the integration of field findings based on UI green city metric indicators and green accounting approaches in the development of village sustainability reporting. This study was conducted in Karangpring village, Jember district, which is a case study village with abundant natural resources and strong local sustainability initiatives. A qualitative case study method was used, employing data collection techniques such as in-depth interviews, field observations, and document analysis. The results of the study show that Karangpring village has implemented various sustainable practices in terms of spatial planning, water management, mobility, waste management, energy, and village governance. However, these efforts have not been fully documented in a structured, accounting-based reporting system. By applying a green accounting approach, this study developed a green village financial report format consisting of a green balance sheet, an environment-based budget realization report, and notes to the green financial statements. This reporting format aims to improve transparency and accountability, as well as support evidence-based environmental policy formulation at the village level. This study contributes to the development of integrated and applicable village sustainability reporting, and opens up opportunities for regulation and digitization of environmental reporting at the local government level.